Doping PCL scaffolds with novel JNK inhibitors to impart anti-inflammatory properties; Химия и химическая технология в XXI веке - Lavrinenko A. K.; Stankevich K. S. Ksenia Sergeevna; Goreninskii S. I. Semen Igorevich; Kovrizhina A. R. Anastasia Ruslanovna; Filimonov V. D. Viktor Dmitrievich; Tverdokhlebov S. I. Sergei Ivanovich (Химия и химическая технология на иностранном языке, 2020)
Заглавие с экрана